THE INFLUENCE OF THE FINANCIAL & BANKING SECTOR ON THE SOCIO-ECONOMIC DEVELOPMENT OF THE REGIONS - A. V. Milenkov (Вестник университета)
The factors of influence of the financial and banking sector on the processes of development of the socio-economic sphere of the regions have been generalized theoretically. Long-term lending (capital loan investment) has been allocated as a fundamentally important factor influencing the development of the economic complex and positive changes in the socio-economic sphere of the region as a whole. The available data on sources of financing of investments in fixed capital of organizations of non-financial sector have been analyzed. The impact on the socio-economic development of regions, which has the implementation of such banking functions as payment and settlement function, lending to the population, Deposit (saving function), the function of currency operations, has been considered. An assessment of a number of negative factors, that had an impact on the development of the financial and banking sector of the country in recent years, has been given.